VEQ’s Summer 2020 Newsletter - Voice of English-speaking Quebec (VEQ) (2020)

VEQ’s Summer 2019 Newsletter - Voice of English-speaking Quebec (VEQ) (2019)

VEQ's Summer 2018 Newsletter - Voice of English-speaking Quebec (VEQ) (2018)

VEQ’s Spring 2020 Newsletter - Voice of English-speaking Quebec (VEQ) (2020)

VEQ’s Spring 2019 Newsletter - Voice of English-speaking Quebec (VEQ) (2019)

VEQ's Spring 2018 Newsletter - Voice of English-speaking Quebec (VEQ) (2018)

VEQ’s Fall Winter 2020 Newsletter - Voice of English-speaking Quebec (VEQ) (2020)

VEQ Newsletter Summer 2021 - Voice of English-speaking Quebec (VEQ) (2021)

VEQ Newsletter Spring 2021 - Voice of English-speaking Quebec (VEQ) (2021)

VEQ Newsletter November 2021 - Voice of English-speaking Quebec (VEQ) (2021)

VEQ Newsletter December 2021 - Voice of English-speaking Quebec (VEQ) (2021)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2014)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2014)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2014)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2015)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2015)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2015)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2016)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2016)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2016)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2017)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2017)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2017)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2018)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2019)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2024)

Travellin' Toddler Time : 2018-2019 Schedule - Voice of English-speaking Quebec (VEQ) (2018)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

The Many Faces of Elder Abuse - Voice of English-speaking Quebec (VEQ)
Voice of English-speaking Québec is proud to support English-speaking seniors in the greater Quebec City region. This booklet was produced to help seniors in our community stay independent, safe and to help prevent abuse and discrimination targeting them. This project is funded in part by Service Canada under the New Horizons for Seniors Program.

The English-speaking Community of the Greater Quebec Region - Voice of English-speaking Quebec (VEQ) (2016)

Report on Youth Employability in the Greater Quebec City Region - Voice of English-speaking Quebec (VEQ) (2020)
In the winter of 2019-2020, we conducted a survey of English-speaking youth aged 15 to 29 as well as six focus groups at the English high schools in the region to support two projects related to youth employability. Through our needs analysis, we sought to evaluate youth knowledge and/or use of the services offered by the Carrefour jeunesse-emploi centres as well as to gain some insights into the postsecondary education and career plans of the students at the local English high schools. These results are meant to provide a snapshot of the perspectives of Englishspeaking youth on employment in the Greater Quebec City region at this time. Though small in scope and sample size (53 survey participants, 32 focus group participants), this study captures the very real hopes and frustrations of our minority population. At the same time, it also proposes some very concrete and achievable outcomes. We hope that this document can serve as a springboard for employers and service providers to work with us, and members of our community, to increase the employability of English-speaking youth in the Greater Quebec City region. Let’s build a better future for all Québécois.

Report : Future Forum of the English-speaking Community - Future Forum of the English-speaking Community (Voice of English-speaking Quebec (VEQ), 2013)
The Future Forum was held on November 24th, 2012 from 9 am - 2 pm at Eastern Québec Learning Center in Quebec City, Québec. The purpose of the event was to share opinions on the current state, needs and challenges of the English-speaking community while generating a shared vision for our future.

Québec Health 101 Guide - Jeffery Hale Community Services; Community Wellness Centre; Voice of English-speaking Quebec (VEQ) (2018)
This guide and the accompanying presentation were developed with the intention of helping newcomers navigate the medical system here in Québec City with a little more ease and efficiency. This project was a joint effort between Jeffery Hale Community Services, the Community Wellness Centre and the Voice of English-speaking Québec. This document was inspired by the Valcartier Family Centre Health Guide.

Presentation to the Standing Senate Committee on Official Languages - Gignac, Jean-Sébastien (2010)

Practice Makes Perfect - Voice of English-speaking Quebec (VEQ) (2019)

Partner Survey 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

Mémoire concernant les consultations particulières et auditions publiques sur le projet de loi no 10 : Loi modifiant l’organisation et la gouvernance du réseau de la santé et des services sociaux notamment par l’abolition des agences régionales - Voice of English-speaking Quebec (VEQ) (2014)
La Voix des Anglophones de Québec (VEQ) est un organisme autonome à but non lucratif dédié à la préservation d’une communauté anglophone dynamique dans la grande région de Québec et à la promotion de ses intérêts. VEQ est gouverné par un conseil d’administration formeé de 15 bénévoles. À ce jour, VEQ maintient des partenariats productifs avec approximativement 70 groupes et institutions et bénéficie du support concret de plus de 2 200 membres.

Membership Socio-demographic Attributes 2010-11 - Voice of English-speaking Quebec (VEQ) (2011)

Listening to Our Young People : The VEQ Youth Report 2005 - Pitre, Edgard; Tomlinson, Patrick; Twardawa, Christopher (Voice of English-speaking Quebec (VEQ), 2005)
The following represents the findings of a youth study conducted by the Voice of English-speaking Québec (VEQ) in 2004 - Listening to Our Young People. The purpose of the study was to collect and correlate survey responses completed by Secondary IV and V, adult learning centre, and CEGEP 1, 2 and 3 Anglophones in the Greater Quebec City and Chaudières-Appalaches regions. The survey questions varied in scope but the general focus was concerned with the various aspects of daily life in and around Quebec City. By analyzing survey responses, VEQ hoped to arrive at a better understanding of the perceptions, positive and otherwise, young Anglophones have regarding their community.

List of Employers in Quebec City Region with Jobs That Require English Skills - Voice of English-speaking Quebec (VEQ)

La communauté d'expression anglaise de la [de la] grande région de Québec - Voice of English-speaking Quebec (VEQ) (2016)

Get Involved, Connected & Meet New People! - Voice of English-speaking Quebec (VEQ)

Financial Statements - Voice of English-speaking Quebec (VEQ) (2019)

Community Consultation 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

Brief Regarding the General Consultation and Public Hearings on Bill 14 : An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Voice of English-speaking Quebec (VEQ) (2013)
The purpose of this brief is to highlight the potential impacts that the proposed Bill 14 could have on the minority English-speaking community of the Greater Quebec City region. As the preeminent interest group representing English-speakers in the Quebec City region, VEQ has carefully analyzed all the modifications included in the proposed Bill 14 and has consulted its membership, community and many of its key partners in order to present this comprehensive evaluation of the impacts that Bill 14 could have on our community. It is our opinion that Bill 14, if adopted in its present form, will have several negative consequences on the vitality of our community and on the capacity of English speakers to continue to be contributing citizens of our region. In addition, we sincerely believe that Bill 14 will also have a real negative impact on the capacity of our entire region to attract and retain English-speaking immigrants and migrants which will directly affect the economic prosperity of the Quebec City region.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2017-2018 - Voice of English-speaking Quebec (VEQ) (2018)

Annual Report 2016-2017 - Voice of English-speaking Quebec (VEQ) (2017)

Annual Report 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

Annual Report 2014-2015 - Voice of English-speaking Quebec (VEQ) (2015)

Annual Report 2013-2014 - Voice of English-speaking Quebec (VEQ) (2014)

Annual Report 2011-2012 - Voice of English-speaking Quebec (VEQ) (2012)

Annual Report 2010-2011 - Voice of English-speaking Quebec (VEQ) (2011)

Annual Report 2009-2010 - Voice of English-speaking Quebec (VEQ) (2010)

Annual Report 2008-2009 - Voice of English-speaking Quebec (VEQ) (2009)

Annual Report 2007-2008 - Voice of English-speaking Quebec (VEQ) (2008)

Annual Report 2006-2007 - Voice of English-speaking Quebec (VEQ) (2007)

A Website Created to Support English-speaking Patients from Eastern Regions in Quebec Traveling Away from Home for Medical Services - Community Health and Social Services Network (CHSSN) (2017)

A Study of Recruitment and Retention Factors Affecting Immigrants, and Anglophone Newcomers in the Quebec City Region - Voice of English-speaking Quebec (VEQ); Conférence régionale des élus de la Capitale-Nationale (2009)
This study focuses on the trends and community-based responses to in-migration in the Quebec City region. It is specifically concerned with issues pertaining to the local English-speaking community, a group that is vested with the legal and political designation of official language minority community by the federal government of Canada. The issue of in-migration is multifaceted and multidisciplinary. To wade into debates on the patterns and effects of migration over a given territory requires a significant amount of background knowledge from a number of different sources. Moreover, to consider the proper policy responses to migratory patterns, we must pay attention to wider political, sociological, and economic conditions that shape how individuals make decisions, such as why they move to a particular region, how long to stay and when to leave.

39th Annual General Meeting - Voice of English-speaking Quebec (VEQ) (2020)

2018-2019 Annual Report - Voice of English-speaking Quebec (VEQ) (2019)